The Role Of Duolingo In Developing Students’ Listening Skills: Students’ Voices - Saltha Aulia Alpika; Dzul Rachman; Rani Herning Puspita (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Information and Communication Technology (ICT) has become a fundamental element of English as a Foreign Language (EFL) training, especially via Mobile-Assisted Language Learning (MALL) applications that enhance listening comprehension. Although prior studies have extensively documented the efficacy of Duolingo for general language acquisition, empirical research that rigorously investigates its impact on listening comprehension in the context of Indonesian higher education is few. This study sought to examine the efficacy of Duolingo in improving EFL students' listening comprehension, emphasizing both educational outcomes and learner experiences. This research utilized a mixed-methods approach, incorporating surveys and semi-structured interviews with first-semester undergraduate English as a Foreign Language students. Quantitative data were subjected to descriptive analysis, while qualitative data underwent thematic analysis to facilitate data triangulation. The results demonstrated that Duolingo effectively facilitated students' listening comprehension via repeated audio exposure, incremental task advancement, vocabulary guidance, and gamified elements that increased motivation and engagement. Students additionally indicated enhancements in pronunciation awareness and general English proficiency. The study, however, revealed significant problems, notably with robotic and unnatural speech, irregular speaking tempo, and restricted exposure to genuine hearing input.This study provides empirical evidence indicating that Duolingo serves most effectively as an adjunct listening tool when combined with classroom instruction, rather than as a standalone learning medium. These findings offer pedagogical implications for the incorporation of MALL applications in EFL listening instruction within Indonesian higher education